Effectiveness of Using Zn Powder and Spongy Cadmium As Reductor on Free Nitrite and Nitrate Analysis Method Validation in Bread Samples by UV-Vis Spectrophotometry - Yussi Pratiwi; Elsa Vera Nanda; Aisyah Kistani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
This research had been carried out on the analysis of nitrite and nitrate in bread by UV-Vis spectrophotometry through a diazotization reaction. The research began by determining the optimum conditions for nitrite analysis while nitrate needs to be reduced using Zn powder or spongy cadmium so it can be analyzed by UV-Vis spectrophotometry. Ionic interference could affect nitrite analysis using UV-Vis spectrophotometry, then both nitrite and nitrate analysis methods were validated based on the method validation parameters. The diazotization reaction produced an azo compound which have λmax 546 nm. The validation results showed that the linearity of nitrite and nitrate has R2 = 0.9990 in the range 0-1 mg L-1 with a molar absorptivity value for nitrite without a reduction process was 3.37 × 104 L mol-1 cm-1, meanwhile 2.91 × 104 L mol-1 cm-1 and 3.83 × 104 L mol-1 cm-1 was shown for the reduced nitrite of Zn powder and spongy cadmium. The detection limits were 4.29 × 10-3, 9.34 × 10-3 ,and 7.58 × 10-3 mg L-1 .The %RSD results were 0.31-1.83% with recovery percentage of nitrite and nitrate in the range of 83.2-104.4%. The strongest ionic interference was shown by Fe2+ and Fe3+ ions at concentrations < 10 mg L-1. WHO has confirmed that the daily intake for nitrate that is acceptable to be consumed by human is 0-3.7 mg/kg.